A framework for automated real time management of container handling equipment - Nguyen, Phuong Ly. (2012)
The predictability in operations coupled with optimizing software have been able to make an automated container terminal functioning like one well-tuned machine with various parts synchronized with each other. To achieve better predictability and better synchronization among different types of container handling equipment in a conventional terminal, we propose a framework for the terminal operation control system which employs a close loop of information flow. Real time equipment status is continuous fed into the control system. Predicted future status will be generated and used by the system dispatchers to make decisions. The dispatchers of different types of equipment will cooperate in a master-slave relationship with the objective of keeping the quay cranes operating as fast as they can. This is to achieve one of the most important objective of container terminal operations: minimization of vessel turnaround time. This is a position paper where some results on some parts of the framework have been published